Out of hospital cardiac arrest survivors with inconclusive coronary angiogram: Impact of cardiovascular magnetic resonance on clinical management and decision-making. (July 2017) - Baritussio, A.; Zorzi, A.; Ghosh Dastidar, A.; Susana, A.; Mattesi, G.; Rodrigues, J.C.L.; Biglino, G.; Scatteia, A.; De Garate, E.; Strange, J.; Cacciavillani, L.; Iliceto, S.; et al.
Abstract: Background: Non-traumatic out of hospital cardiac arrest (OHCA) is the leading cause of death worldwide, mainly due to acute coronary syndromes. Urgent coronary angiography with view to revascularisation is recommended in patients with suspected acute coronary syndrome. Diagnosis and management of patients with inconclusive coronary angiogram (unobstructed coronaries or unidentified culprit lesion) is challenging. We sought to assess the role of Cardiovascular Magnetic Resonance (CMR) in the diagnosis and management of OHCA survivors with an inconclusive coronary angiogram. Methods and results: This is a retrospective multicentre CMR registry analysis of OHCA survivors with an inconclusive angiogram. Clinical, ECG and multi-modality imaging data were analysed. Clinical impact of CMR was defined as a change in diagnosis or management. Out of 174 OHCA survivors referred for CMR, 110 patients (63%, 84 male, median age 58) had an inconclusive angiogram. CMR identified a pathologic substrate in 76/110 patients (69%): ischemic heart disease was found in 45 (41%) and non-ischemic heart disease in 31 (28%). A structurally normal heart was found in 25 patients (23%) and non-specific findings in 9 (8%). As compared to trans-thoracic echocardiogram, CMR proved to be superior in identifying a pathologic substrate (69% vs 54%, p = 0.018). The CMR study carried a clinical impact in 70% of patients, determining a change in diagnosis in 25%, in management in 29% and a change in both in 16%. Conclusions: CMR showed a promising role in the diagnostic work-up of OHCA survivors with inconclusive angiogram and its wider use should be considered.